Mediterranean Gluten-Free Diet: Is It a Fair Bet for the Treatment of Gluten-Related Disorders? - Bascuñán, Karla A.; Elli, Luca; Vecchi, Maurizio; Scricciolo, Alice; Mascaretti, Federica; Parisi, Maria; Doneda, Luisa; Lombardo, Vincenza; Araya, Magdalena; Roncoroni, Leda (Frontiers in Nutrition, 2020)
Purpose: The gluten-free diet (GFD) is the current treatment of gluten-related disorders that eliminates wheat, barley, and rye, while the exclusion of oats is still under debate. GFD is based on a combination of naturally gluten-free foods and gluten-free substitutes of cereal-based foods. Although effective as a treatment of gluten-related disorders, it poses some nutritional caveats that remain under debate, mainly how to improve some nutrient deficiency and other concerns such as increasing overweight in some patients. The “Mediterranean diet” (MedD) refers to the dietary pattern and eating habits typical of populations living in the Mediterranean basin, which have been associated with a low prevalence of diverse diet-related pathologies. In this review article, we summarize current knowledge about GFD and MedD, their characteristics, and central food components. Methods: We conducted a search of various databases, such as PubMed, Embase, Scielo, and Google Scholar with focus on keywords such as "Celiac disease", "Gluten-free diet", "Mediterranean diet", "Food Pyramid", "Cereals" and, "Pseudocereals". Conclusion: The MedD pyramid has been adapted to the culinary culture of several countries with diverse feeding habits. The MedD pyramid can be followed by individuals that need excluding dietary gluten. Based on the reported positive health effects of the MedD we propose a fusion between the Mediterranean diet and the GFD, which seems an attractive alternative to reach a gluten-free healthy diet clearly benefiting those who practice it.